Efektivitas Penggunaan Media Virtual Lab dalam Pembelajaran Kimia pada Materi Larutan Elektrolit dan Nonelektrolit SMA Negeri 1 Wewewa Barat T.P 2025/2026 - Falentina Lede; Ni Wayan Prawita Aryani; Selviana Bulu (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effectiveness of using Virtual Lab media in chemistry learning on the topic of electrolyte and nonelectrolyte solutions at SMA Negeri 1 Wewewa Barat in the 2025/2026 academic year. The study was motivated by students' low learning outcomes on this topic and the need for instructional media capable of enhancing conceptual understanding through interactive virtual laboratory activities. A quasi-experimental method with a Pretest–Posttest Control Group Design was employed. The research sample consisted of two groups, namely an experimental group and a control group, each comprising 20 students. The experimental group was taught using Virtual Lab media, while the control group received conventional instruction. The research instrument was a learning achievement test administered as both a pretest and a posttest. The data were analyzed using normality, homogeneity, and independent samples t-tests at a 5% significance level. The results showed that both groups had the same mean pretest score (43.75), indicating equivalent initial abilities. After the treatment, the mean posttest score of the experimental group increased to 82.75, while the control group achieved a mean score of 69.25. The improvement in learning outcomes was 39.00 points in the experimental group, exceeding the 25.50-point improvement observed in the control group. The normality test indicated that the experimental group's pretest and posttest data were normally distributed, whereas the control group's data showed slight deviations from normality. Nevertheless, the analysis was continued because both groups had equal sample sizes and homogeneous variances, with a significance value of 0.272. The hypothesis test yielded a calculated t-value of 9.69, which was greater than the critical t-value of 1.686 at the 0.05 significance level (df = 40), leading to the rejection of the null hypothesis and acceptance of the alternative hypothesis. Therefore, it can be concluded that the use of Virtual Lab media is effective in improving students' learning outcomes on the topic of electrolyte and nonelectrolyte solutions. Compared with conventional instruction, Virtual Lab had a significant positive effect and can serve as an innovative and effective alternative medium for chemistry learning.